Redox-mediated 3D graphene based nanoscoop design for ultracapacitor applications - Rani, Pallavi; Jhajharia, Suman Kumari; Selvaraj, Kaliaperumal (New Journal of Chemistry, 2017)
Contemporary energy storage devices significantly rely on the rational design of micro and nanostructural features of electrode materials for efficient ion transport. A judicious concept of utilizing the extended charge mobility on the third dimension along with an active redox couple to significantly maximize the capacitance has been demonstrated via (a) the fabrication of a 3D network from 2D graphene and (b) the introduction of an active redox species. Compared with traditional graphene systems, an unprecedented 8-fold gain of capacitance that was sustained with minimal loss even beyond 5000 cycles is achieved and is reported for the first time. This was due to the complementary advantage of both the electric double layer capacitance of the 3D graphene electrode and the redoxmediated pseudocapacitance of K3Fe(CN)(6) in alkaline electrolytes. Colloidal polystyrene spheres with a tunable size range were used as sacrificial templates for generating the 3D network. This design outperforms others, is an excellent candidate as an ultracapacitor and is envisaged to lead to new opportunities in several electrochemical applications.

Removal of fluoride from aqueous solution by mesoporous silica nanoparticles functionalized with chitosan derived from mushroom - Srivastava, Anushree; Kumari, Madhu; Ramanathan, Alagappan; Selvaraj, Kaliaperumal; Prasad, Bablu; Prasad, Kumar Suranjit (Journal of Macromolecular Science Part A-Pure and Applied Chemistry, 2020)
In the present study, chitosan functionalized mesoporous silica nanoparticles have been synthesized. Chitosan derived from an edible mushroom, Agaricus bisporus was used during synthesis of chitosan functionalized silica nanoparticles. The functionalized silica nanoparticles were subjected to fluoride sorption using a batch method which subsequently showed removal efficiency of 95% with maximum sorption capacity, 58.8 mg/g. The characterization of nanoparticles was carried out by SEM, EDAX, XRD and FTIR analysis respectively. EDAX analysis suggested that oxygen, 51.83% and silica 37.24% was main constituent of the functionalized nanomaterials. XRD yielded characteristic diffraction pattern corresponding to the lattice planes (100), (110), (112), (120), (200) and (220) respectively. Sorption data was used to study equilibrium isotherm namely Langmuir and Freundlich model. The adsorption capacity increased with temperature while kinetics studies revealed that the adsorption process followed a pseudo-second-order rate equation. The enthalpy change (Delta H) and entropy change (Delta S) was found to be -31.36 kJmol(-1) and -7.75 Jmol(-1) K-1, showing endothermic and spontaneous nature of the fluoride adsorption. Data suggested that the nature of adsorption belonged to chemisorptions. The overall results suggested that the synthesized nanoparticles showed strong and specific affinity for fluoride and could be excellent adsorbents for defluoridation.
Keywords: Adsorption; Chitosan; EDAX; Fluoride; SEM

Rational design of hydrophobic Cu/CuO electrodes for electrochemical oxygenation of tetralin: a strategic approach - Cherukuthota, Sri Vidya; Mathew, Elizabeth; Verma, Tushar Singh; Joshi, Krati; Selvaraj, Kaliaperumal (ChemSusChem, 2025)
Electro-organic synthesis presents a sustainable and practical alternative to traditional organic synthesis methods, which typically utilize harsh reagents and require energy-intensive conditions. Nevertheless, the challenge of achieving satisfactory conversion and selectivity rates in electrocatalytic oxidation using a non-platinum group metal (PGM) catalyst pair still needs to be addressed. This study demonstrates the application of a non-PGM-based catalyst pair for the electrocatalytic oxidation of tetralin to 1-tetralone, a highly demanded raw material in the pharma industry. Copper electrodeposited on teflonated carbon paper combined with copper foam as the electrocatalyst pair has demonstrated impressive conversion and selectivity ratios to electro-synthesize 1-tetralone at room temperature and atmospheric pressure. The optimal choice of a non-PGM catalyst, ideal mass loading, and a unique electrode configuration resulted in an ultimate conversion of about 99% of tetralin and 1-tetralone selectivity -93.7%, yield -92.6%. The reaction pathway associated with the electrochemical phenomena is supported by first principles-based density functional theory calculations and X-ray photoelectron spectroscopy of the electrocatalyst. This process has exceptional performance that can be adapted for a wide range of substrates and is straightforward, ambient, reagent-free, scalable, and therefore beneficial for industrial use. Therefore, initiatives have been taken in this direction.
Keywords: C-H activation; Copper; electrochemical oxidation; non-PGM electrocatalysts; tetralin; Tetralone